Diagnostic accuracy of B-scan in predicting retinoblastoma in children, taking Magnetic Resonance Imaging of orbits as gold standard - Saba Murad; Ishtiaq Ahmed; Hania Ali; Maria Ghani; Sana Murad (Journal of the Pakistan Medical Association, 2020)
The objective of this study was to determine the diagnostic accuracy of B-scan in predicting retinoblastoma (Rb) taking Magnetic Resonance Imaging (MRI) as a gold standard. A cross-sectional validation study was conducted in the Radiology Department of Fauji Foundation Hospital from May 20 to Nov 20, 2017. Children fulfilling the inclusion criteria were selected after informed consent and detailed history was taken for investigation of Rb. B-scan of both eyes was done using 7.5-10 MHz probe, followed by MRI of both eyes in the same patients using 1.5 Tesla MRI machine with the help of qualified MRI technicians. Data analysis was done by SPSS version 16.0. The diagnostic accuracy, sensitivity, specificity, PPV and NPV of B-scan in prediction of Rb as compared to MRI was 90.45%, 82.28%, 90.54% and 90.28% respectively. The study concluded that diagnostic accuracy of B-scan as compared to MRI is substantial in Retinoblastoma. Continuous...